Twelve‐month‐old infants' physiological responses to music are affected by others' positive and negative reactions. (13th June 2021) - Fawcett, Christine; Kreutz, Gunter
Abstract: Infants show remarkable skills for processing music in the first year of life. Such skills are believed to foster social and communicative development, yet little is known about how infants' own preferences for music develop and whether social information plays a role. Here, we investigate whether the reactions of another person influence infants' responses to music. Specifically, 12‐month‐olds ( N  = 33) saw an actor react positively or negatively after listening to clips of instrumental music. Arousal (measured via pupil dilation) and attention (measured via looking time) were assessed when infants later heard the clips without the actor visible. Results showed greater pupil dilation when listening to music clips that had previously been reacted to negatively than those that had been reacted to positively (Exp. 1). This effect was not replicated when a similar, rather than identical, clip from the piece of music was used in the test phase (Exp. 2, N  = 35 12‐month‐olds). There were no effects of the actor's positive or negative reaction on looking time. Together, our findings suggest that infants are sensitive to others' positive and negative reactions not only for concrete objects, such as food or toys, but also for more abstract stimuli including music.